The EMBL Nucleotide Sequence Database - Stoesser, Guenter (Oxford University Press, 2002)
The EMBL Nucleotide Sequence Database (aka EMBL-Bank; http://www.ebi.ac.uk/embl/) incorporates, organises and distributes nucleotide sequences from all available public sources. EMBL-Bank is located and maintained at the European Bioinformatics Institute (EBI) near Cambridge, UK. In an international collaboration with DDBJ (Japan) and GenBank (USA), data are exchanged amongst the collaborating databases on a daily basis. Major contributors to the EMBL database are individual scientists and genome project groups. Webin is the preferred web-based submission system for individual submitters, whilst automatic procedures allow incorporation of sequence data from large-scale genome sequencing centres and from the European Patent Office (EPO). Database releases are produced quarterly. Network services allow free access to the most up-to-date data collection via FTP, email and World Wide Web interfaces. EBI’s Sequence Retrieval System (SRS), a network browser for databanks in molecular biology, integrates and links the main nucleotide and protein databases plus many other specialized databases. For sequence similarity searching, a variety of tools (e.g. Blitz, Fasta, BLAST) are available which allow external users to compare their own sequences against the latest data in the EMBL Nucleotide Sequence Database and SWISS-PROT. All resources can be accessed via the EBI home page at http://www.ebi.ac.uk.